Community education about stunting in Neglasari Village Tasikmalaya Regency - Priyadi, Agim Agustiar; Julkipli, Ahmad; Rasim, R. (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
Stunting is a problem of malnutrition caused by providing food that does not meet nutritional needs. It also reflects stunted growth due to poor nutrition and poor health before and after birth. Based on service in Neglasari Village, the main problem was identified: the lack of public understanding about stunting and related information. Even though the stunting rate in Neglasari Village is relatively low, it is essential to create awareness and preventive efforts. Therefore, this service aims to educate the people of Neglasari Village, Salawu District, and Tasikmalaya Regency regarding stunting. The method applied in this service is counseling for one month at every Posyandu in Neglasari Village. The service team provides education in collaboration with village officials and community health centers to conduct outreach related to stunting in Neglasari Village. Based on the results of the service implementation, it can be concluded that there is still a lack of public awareness regarding nutritional aspects, economic factors, exclusive breastfeeding, complementary feeding, and genetic factors of parents in Neglasari Village. It is hoped that implementing this service activity will be an effort to reduce stunting rates in Indonesia.